A 1-Gbps IR-UWB pulse generator for 802.11a and WiMAX interference avoidance - Al-Khateeb, Khalid A. Saeed; Mohammed, Ahmed R. (2011)
A novel design is proposed for a I-Gbps Impulse Radio lJltra Wideband (IR-lJWB) pulse generator. The generated pulse is not just suitable for solving the problem of UWB interference with Wireless Local Area Network (WLAN) 802.11a and Worldwide Interoperability for Microwave Access (WiMAX) systems, but it has no interference on any narrowband system works below 3.1GHz. The spectrum of the pulse satisfies the requirements of the Federal Communication Commission (FCC) UWB indoor as well as outdoor mask. The interference mitigation on WiMAX band is less than -80dBmlMHz. Interference on 802.11a band is avoided by adjusting a spectral notch of less than -85dBm/MHz at 5GHz. The pulse generator uses a single two ports parallel coupled microstrip line as a bandpass filter (BPF). The same pulse generator can be used for Pulse Position Modulation (PPM) or On-Off Keying (OOK).